Effect of high-intensity, short-duration grazing on species density and botanical composition of arid rangelands - Louhaichi, Mounir; Gamoun, Mouldi; Gouhis, Fethi; Belfekih, Ezzeddine; Abdelkader, Mohamed (Kenya Agricultural and Livestock Research Organization, 2022)
Rangelands are the mainstay of pastoral and agropastoral livelihoods worldwide. They have provided forage for livestock and wildlife for centuries, but steady degradation of rangelands is causing increasing concern. Many rangeland managers believe exclusion of livestock grazing for extended periods would allow degraded rangelands to recover. The purpose of this current ongoing research is to evaluate the effect of high-intensity short-duration grazing on plant density, species richness and botanical composition on arid rangelands during favorable years. The site, which is protected for two years in southern Tunisia and covers an area of 6 ha, was grazed by a flock of about 150 heads of sheep for one week. The grazing took place towards the end of the spring season just after seed dispersal. The measurements were taken before and after grazing using the quadrats method. Preliminary findings revealed no significant difference in plant density, richness, and botanical composition of perennial species. On the contrary, the annual species decreased. In conclusion, short-duration grazing systems do not affect perennial plants that permit greater forage selectivity. As temperatures start rising in late spring, livestock is forced to select annual plants due to their higher palatability and higher water content without damaging perennial plants. In addition, grazing removes oxidized plant material from perennial species that would otherwise remain on top of the plants, prevent photosynthesis, and cause the plant’s death after several years.